Análise de determinantes de matrículas em cursos superiores EAD - Forte, Celiane Guilherme Sampaio (2021)
Distance higher education in Brazil has been growing a lot over the years, especially since 2017. Institutions and institutions are responsible for most of the offer of courses. The academic degree with the largest number of on-site courses is the baccalaureate and distance education courses is the technological degree. According to the estimated econometric model, the number of enrollments in distance learning courses is positively related to the number of distance learning centers, income and monthly income. The exponential smoothing model rates indicate that there is an increasing trend for the number of enrollments over the years, and it is possible to double the value from 2019 to 2027.